2012
DOI: 10.1177/0042085911429974
|View full text |Cite
|
Sign up to set email alerts
|

Science and the City

Abstract: The purpose of this article is to describe several conceptual areas that warrant attention by scholars and practitioners interested in improving access and opportunity to science, technology, engineering, and mathematics (STEM) learning in urban cities. Thinking conceptually about the urban context has been a part of intellectual traditions in the social sciences for decades. Like in other fields of study, for example, economics, sociology, and political science, the treatment of urban communities as unique ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…However, ethnic groups traditionally underrepresented in STEM continue to be underrepresented in AP Chemistry participation. This is consistent with research that has shown that schools serving predominantly high-poverty students and ethnic minorities underrepresented in STEM have limited access to advanced sciences, 86,87 yet much of this research has focused on the sciences in general or physics specifically. 10,11,[20][21][22]88 Research has shown schools serving White and Asian students have had greater expansion of AP programs compared to schools serving Black and Hispanic students, perpetuating the disparities in access and enrollment in AP coursework.…”
Section: Ap Chemistry Performancesupporting
confidence: 87%
“…However, ethnic groups traditionally underrepresented in STEM continue to be underrepresented in AP Chemistry participation. This is consistent with research that has shown that schools serving predominantly high-poverty students and ethnic minorities underrepresented in STEM have limited access to advanced sciences, 86,87 yet much of this research has focused on the sciences in general or physics specifically. 10,11,[20][21][22]88 Research has shown schools serving White and Asian students have had greater expansion of AP programs compared to schools serving Black and Hispanic students, perpetuating the disparities in access and enrollment in AP coursework.…”
Section: Ap Chemistry Performancesupporting
confidence: 87%
“…These might constrain children’s initial science achievement as well as science achievement growth (Pong, Dronkers, & Hampden-Thompson, 2003). Young, struggling readers often acquire lower vocabularies (and in particular, less abstract, technical, or “academic” vocabularies often used during science instruction), have less general knowledge, display less cognitive ability (Cunningham & Stanovich, 1997), and are often less able to comprehend science texts and generate science-related inferences (Tate, Jones, Thorne-Wallington, & Hogrebe, 2012). In contrast, O’Reilly and McNamara (2007) found that being a skilled reader helped compensate for a lower level of background knowledge about science among older children.…”
Section: Modifiable Factors Hypothesized To Explain Science Achievement Gapsmentioning
confidence: 99%
“…Substantial attention has already been focused on the need for such early childhood programs (e.g., Head Start, Early Reading First) to address emergent literacy and numeracy gaps during this early time period, as these gaps have been repeatedly established as highly predictive of later reading and mathematics achievement gaps (e.g., Chatterji, 2006;Downey, von Hippel, & Broh, 2004;Foster & Miller, 2007;Jordan, Kaplan, Ramineni, & Locuniak, 2009). Yet little attention has been given to the need to also address science achievement gaps during the preschool or early-elementary time periods (Tate et al, 2012). This is despite repeated and increasingly urgent calls for education policymakers and practitioners to work to prevent low science achievement from threatening the nation's economic competitiveness and the electorate's understanding of public policy issues (NASNAEIM, 2010(NASNAEIM, , 2011.…”
Section: Study's Contributions and Implicationsmentioning
confidence: 99%
“…45 This may be exacerbated when working in urban and rural schools of low socioeconomic status, where external sociocultural factors influence classroom dynamics and student performance. 4,54 These factors may have a cumulative impact on chemistry teachers' self-efficacy, satisfaction, resilience, and commitment to the profession.…”
Section: Journal Of Chemical Educationmentioning
confidence: 91%